2008
DOI: 10.1091/mbc.e06-01-0088
|View full text |Cite
|
Sign up to set email alerts
|

Paxillin Phosphorylation Controls Invadopodia/Podosomes Spatiotemporal Organization

Abstract: In Rous sarcoma virus (RSV)-transformed baby hamster kidney (BHK) cells, invadopodia can self-organize into rings and belts, similarly to podosome distribution during osteoclast differentiation. The composition of individual invadopodia is spatiotemporally regulated and depends on invadopodia localization along the ring section: the actin core assembly precedes the recruitment of surrounding integrins and integrin-linked proteins, whereas the loss of the actin core was a prerequisite to invadopodia disassembly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(119 citation statements)
references
References 58 publications
5
114
0
Order By: Relevance
“…Indeed, Src is also a main regulator of the disassembly of focal adhesions and podosomes ( ; Destaing , 2008et al Webb , 2004 ). A similar pattern has been observed in case of knock-down of many components of Luxenburg , 2006et al Destaing , 2008 podosome ring such as paxillin ( ), meaning that the incapacity to form ring or belt is the signature of a defect in Badowski , 2008 et al podosome type adhesion dynamics. Similarly to podosome distribution during osteoclast differentiation, in RSV-transformed BHK cells, invadopodia can also self-organize into rosettes and belts, under the control of tyrosine phosphorylation whereas in carcinoma cells invadopodia remain as individual structures.…”
Section: Disassembly Of Cell-matrix Adhesionssupporting
confidence: 68%
See 1 more Smart Citation
“…Indeed, Src is also a main regulator of the disassembly of focal adhesions and podosomes ( ; Destaing , 2008et al Webb , 2004 ). A similar pattern has been observed in case of knock-down of many components of Luxenburg , 2006et al Destaing , 2008 podosome ring such as paxillin ( ), meaning that the incapacity to form ring or belt is the signature of a defect in Badowski , 2008 et al podosome type adhesion dynamics. Similarly to podosome distribution during osteoclast differentiation, in RSV-transformed BHK cells, invadopodia can also self-organize into rosettes and belts, under the control of tyrosine phosphorylation whereas in carcinoma cells invadopodia remain as individual structures.…”
Section: Disassembly Of Cell-matrix Adhesionssupporting
confidence: 68%
“…The lack of paxillin phosphorylation, or calpain or Erk inhibition result in similar phenotype, suggesting that these proteins belong to the same regulatory pathways ( ). Surprisingly, this mechanism Badowski , 2008 et al seems to be quite similar in focal adhesions where paxillin also plays a major role in their disassembly ( ). Indeed, Zaidel-Bar , 2007 et al recent studies have demonstrated that the calpain family has a regulatory function in cell motility, partly through the capacity to down regulate integrin-mediated adhesion complexes ( ; ; ; ).…”
Section: Disassembly Of Cell-matrix Adhesionsmentioning
confidence: 99%
“…And Src is also required for invadopodia formation in human breast cancer cells (Artym et al, 2006;Cortesio et al, 2008). In keeping with a role for Src in podosome/invadopodia formation, many Src substrates are obligate podosome components, including cortactin, AFAP110, paxillin, p130Cas, ASAP1, and dynamin (Baldassarre et al, 2003;Brabek et al, 2004;Gatesman et al, 2004;Webb et al, 2006;Bharti et al, 2007;Clark et al, 2007;Badowski et al, 2008).…”
Section: Introductionmentioning
confidence: 93%
“…Both Src and cortactin are essential for invadopodia formation and their increased activity can be used as a potential marker for the onset of invadopodia formation [204,205]. Downstream targets of activated Src which are known to be essential for invadopodia formation and maintenance include cortactin, N-WASP, ArfGAPs like AMAP1/AMAP2, paxillin and Tks5/Fish [197,[206][207][208][209].…”
Section: Podosomes and Invadopodiamentioning
confidence: 99%